Pengaruh Brand Image Dan Brand Trust Terhadap Brand Loyalty Dan Terhadap Purchase Decision (Studi Pada Mahasiswa/I Pengguna Deodoran Nivea Di Kota Semarang) - Nabilla Rafa Shakila Soesanto; Bambang Sutedjo; Sri Sumiyati, Hari Sucahyowati (SEIKO : Journal of Management & Business, 2025)
The purpose of this study was to analyze the influence of brand image and brand trust on brand loyalty and purchasing decisions. The population in this study were students who used Nivea deodorant in Semarang City. This study used a quantitative approach by distributing questionnaires to 87 respondents. Data were analyzed using multiple regression. The results showed that brand image and brand trust had a positive and significant effect on brand loyalty. Brand loyalty also had a positive and significant effect on purchasing decisions. Keywords : brand image; brand trust; brand loyalty; purchase decision